Investigating on job hopping behavior among restaurant employees in Malaysia - Ghazali, Hazrina; Roslan, Nur Nabiha (Asian Economic and Social Society, 2020)
Job hopping behavior among employees has existed ever since the inception of the industry. Today, in well-developed restaurant industry, job hopping is viewed as a typical practice among employees. When many options of job vacancy became available, an employee left an organization that cannot match with his expectations and move to another organization. However, this job hopping behavior was considered as normal behavior. As employees are considered a major capital for any organization, the relationship on job-hopping behavior with employees need to be investigated. The researcher sheds light on this situation from the manager’s point of view. This research aims to identify the reasons of job hopping behavior among employees. This research employed qualitative approach by using face-to-face interview. The data was gathered through semi-structured interview and a total of 10 restaurant managers from casual dining restaurants were voluntarily participated and interviewed in this research. Based on the interview data, it revealed six reasons that associated with employees’ job hopping which include financial and benefit, career growth, job security, social influences, working environment and low passion for jobs. Findings of this research hoped will help the restaurant owner and human resource division to highlight factors that lead to job hopping behavior. Additionally, findings of this study also expected to provide a better understanding to formulate effective measures and ultimately minimize job hopping from occur in the restaurants.